2019
DOI: 10.31221/osf.io/w958z
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of heavy metals in tobacco of cigarettes commonly sold in Ethiopia

Abstract: A significant flux of heavy metals, among other toxins, reaches the lungs through smoking. This study reports Cd, Pb, Cu and Zn contents in tobacco of 11 brands of cigarette commonly sold in Ethiopia. The heavy metals were determined by atomic absorption spectrophotometry after wet digestion of cigarette tobacco using HNO3 and H2O2. The concentration of trace metals in the cigarettes ranged (mean) (μg/g), Cd: 1.3−7.6 (2.48±0.32), Pb: 0.50−12.50 (6.24±2.2), Cu: 2.89−25.35 (13.70±4.12) and Zn: 24.40−62.55 (36.22… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
1
0
1
Order By: Relevance
“…Similar results were observed with Hg (Phal 2011;Kowalski and Wierciński 2009;Raju et al 1999). Whereas the Fe (Dobaradaran et al 2017;Engida and Chandravanshi 2017;Sebiawu et al 2014;Raju et al 1999), Cd (Dobaradaran et al 2017;Janaydeh et al 2019;Engida and Chandravanshi 2017;Sebiawu et al 2014;Ashraf 2012;Eneji et al 2013;Kazi et al 2009;Raju et al 1999) content reported in the present was comparatively lesser. This may be due to the difference in leaching methods employed and the number of samples used.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar results were observed with Hg (Phal 2011;Kowalski and Wierciński 2009;Raju et al 1999). Whereas the Fe (Dobaradaran et al 2017;Engida and Chandravanshi 2017;Sebiawu et al 2014;Raju et al 1999), Cd (Dobaradaran et al 2017;Janaydeh et al 2019;Engida and Chandravanshi 2017;Sebiawu et al 2014;Ashraf 2012;Eneji et al 2013;Kazi et al 2009;Raju et al 1999) content reported in the present was comparatively lesser. This may be due to the difference in leaching methods employed and the number of samples used.…”
Section: Discussionsupporting
confidence: 86%
“…The mean amount was found to be 16.85 µg/g with a minimum amount of 0.834 µg/g and a maximum of 128.893 µg/g and the amount was found to be more in the leachates of the cigarette sample. This was much higher than other reports (Janaydeh et al 2019;Engida and Chandravanshi 2017;Sebiawu et al 2014;Ashraf, 2012;Kazi et al 2009;Raju et al 1999). In the present study, a mean of 78.98 µg/g of copper with a maximum of 287.52 µg/g was observed and this level was several folds higher than other reports (Dobaradaran et al 2017;Engida and Chandravanshi 2017;Sebiawu et al 2014;Raju et al 1999).…”
Section: Discussioncontrasting
confidence: 56%